GABAergic Mechanisms in Schizophrenia: Linking Postmortem and In Vivo Studies - de Jonge, Jeroen C.; Vinkers, Christiaan H.; Hulshoff Pol, Hilleke E.; Marsman, Anouk (Frontiers in Psychiatry, 2017)
Schizophrenia is a psychiatric disorder characterized by hallucinations, delusions, disorganized thinking, and impairments in cognitive functioning. Evidence from postmortem studies suggests that alterations in cortical γ-aminobutyric acid (GABAergic) neurons contribute to the clinical features of schizophrenia. In vivo measurement of brain GABA levels using magnetic resonance spectroscopy (MRS) offers the possibility to provide more insight into the relationship between problems in GABAergic neurotransmission and clinical symptoms of schizophrenia patients. This study reviews and links alterations in the GABA system in postmortem studies, animal models, and human studies in schizophrenia. Converging evidence implicates alterations in both presynaptic and postsynaptic components of GABAergic neurotransmission in schizophrenia, and GABA may thus play an important role in the pathophysiology of schizophrenia. MRS studies can provide direct insight into the GABAergic mechanisms underlying the development of schizophrenia as well as changes during its course.